Cytokine gene polymorphisms associated with symptomatic parvovirus B19 infection. Issue 10 (26th September 2003) - Kerr, J R; McCoy, M; Burke, B; Mattey, D L; Pravica, V; Hutchinson, I V
Abstract : Background: The immune system has been implicated in the pathogenesis of certain clinical manifestations of parvovirus B19 infection, including rash and arthralgia. Cytokines feature in the pathogenesis of parvovirus B19 infection, so inherited variability in cytokine responses to B19 infection might have a bearing on the symptomatology of parvovirus B19 infection. Aims: To investigate the possible role of cytokine gene polymorphisms in the clinical manifestations of parvovirus B19 infection. Methods: Thirty six patients with a variety of symptoms at acute infection and follow up (mean, 22.0 months) and controls (99–330, depending on the locus) were examined for the following cytokine polymorphisms: tumour necrosis factor α (TNFα), −308; interferon γ (IFN-γ), +874; interleukin 6 (IL-6), −174; IL-10, −592, −819, and −1082; and transforming growth factor β1 (TGFβ1), +869 (codon 10) and +915 (codon 25). Results: The TNFα −308*A allele occurred in 13.9% of the parvovirus group compared with 27.0% of the control group (odds ratio (OR), 0.44; p = 0.02). The TGFβ1 CG/CG haplotype was more frequent in the parvovirus group than in the controls (16.7% v 5%; OR, 4.8; p = 0.02). Within the B19 infected group, the TGFβ1 +869 T allele was associated with skin rash at acute infection (p = 0.005), whereas at follow up the IFN-γ +874 T allele was associated with the development of anti-B19 non-structural protein 1 antibodies (p = 0.04). Conclusions: The results of the present study suggest that inherited variability in cytokine responses may affect the likelihood of developing symptoms during parvovirus infection.